2018
DOI: 10.3892/ol.2018.7913
|View full text |Cite
|
Sign up to set email alerts
|

Oncological safety of nipple-sparing mastectomy in young patients with breast cancer compared with conventional mastectomy

Abstract: Although nipple-sparing mastectomy (NSM) is being used more frequently, the oncological safety of NSM remains unclear, particularly in young patients (<35 years). The aim of the present study was to compare the rates of local recurrence (LR), disease-free survival (DFS) and overall survival (OS) in young patients with breast cancer who had undergone NSM or conventional mastectomy (CM). The clinicopathological data of young patients with stage 0–IIB breast cancer who had undergone NSM (163 cases) or CM (194 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The result of a retrospective study showed that there were no significant differences in local recurrence, disease-free survival and overall survival between nipple-preserving mastectomy and mastectomy in females aged <35 years. 29 Breast reconstruction for young breast cancer patients can be planned according to the age at diagnosis, the type of breast structure (compact or fat), tumor staging, and adjuvant therapy. Patients with advanced stages and poor prognosis need to be carefully evaluated for breast reconstruction.…”
Section: Oncoplastic Surgery and Breast Reconstructionmentioning
confidence: 99%
“…The result of a retrospective study showed that there were no significant differences in local recurrence, disease-free survival and overall survival between nipple-preserving mastectomy and mastectomy in females aged <35 years. 29 Breast reconstruction for young breast cancer patients can be planned according to the age at diagnosis, the type of breast structure (compact or fat), tumor staging, and adjuvant therapy. Patients with advanced stages and poor prognosis need to be carefully evaluated for breast reconstruction.…”
Section: Oncoplastic Surgery and Breast Reconstructionmentioning
confidence: 99%